Effectiveness of the Implementation of Law No. 33 of 2014 on Halal Product Guarantee on the Compliance of Food and Beverage Vendors in Sapen Yogyakarta - Nengsi Warna Sari; Ulan Fitriyani (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
This study aims to analyze the effectiveness of the implementation of Law Number 33 of 2014 concerning halal product guarantees and its influence on merchant compliance in Sapen Village, Yogyakarta. The phenomenon of low compliance among traders is an important issue because the Sapen area, which is located in a religious environment close to Islamic educational institutions, still has traders who do not have halal certificates or do not display halal labels on their products. This study uses a field research method with an empirical juridical approach to examine the application of law in social reality. Primary data was obtained through observation, interviews with 15 merchants, consisting of 8 kiosk merchants and 7 cart merchants, and through documentation. Meanwhile, secondary data was obtained from literature reviews. Data analysis used qualitative analysis techniques through the stages of reduction, presentation, verification, and conclusion drawing. The results of the study show that the compliance of traders in Sapen with halal certification requirements still varies and does not fully comply with the provisions of Law No. 33 of 2014. This condition is influenced by the ineffective implementation of Law No. 33 of 2014, especially in terms of legal substance, which does not include strict sanctions for traders without halal certificates. while the tendency for compliance among traders is more a matter of compliance (compliance due to fear of sanctions). Law enforcement has also not been maximized, as evidenced by the lack of socialization, supervision, and enforcement of sanctions for traders who are halal certified but do not display the halal label. Furthermore, supporting facilities and infrastructure are available but not evenly distributed, and cultural and societal factors indicate that many merchants still believe in halal without the need for official certification, and consumers tend not to question halal status. Keywords: Legal Effectiveness, Merchant Compliance, Halal Product Guarantee.